Single-cell RNA sequencing shows the immunosuppressive landscape and tumor heterogeneity of HBV-associated hepatocellular carcinoma - Daniel Wai-Hung Ho (Nature Portfolio, 2021)
Different cells of the tumour microenvironment in HBV-associated human hepatocellular carcinoma (HCC) interact to promote tumour immunity. Here the authors use single cell RNA sequencing to identify TIGIT-NECTIN2 as a pathway by which tumour-associated macrophages reduce intratumour T cell activation.